Morphological Variation Interest on Several Varieties of Chrysanthemum morifolium Ramat - Hery Purnobasuki; Anika Sindhya Dewi; Dwi Kusuma Wahyuni (Natural B, Journal of Health and Environmental Sciences, 2014)
The aim of this research was to know the morphological variety of flower in Chrysanthemum morifolium Ramat through visual observation which use digital camera and then was analyzed descriptively. Varieties of Chrysanthemum morifolium Ramat in this research were C. morifolium var reagen pink, C. morifolium var puma purple, C. morifolium var evergreen, C. morifolium var boris becker, C. morifolium var stroika, C. morifolium var tiger, C. morifolium var remix purple, C. morifolium var jaguar red, C. morifolium var rhino white, C. morifolium var pasopati, C. morifolium var towntalk. From those 11 varieties showed the morphological differences of the flowers, which are the color of ray floret, the quantity of ray floret, the quantity of ray floret layers, the shape of ray floret, the tip of ray floret, the quantity of disk floret, the position of disk floret, the diameter of flower, the length of ray floret, the width of ray floret, the diameter of involucrum and the disk shape. However, this research also look the similarities between the varieties, which are the edge of ray floret (flat), the color of involucrum is green, the adhering of inter-involucrum (star like), the tip of involucrum (dull), transparent coating involucrum, the quantity of involucrum layers (2 layers), the color of the corolla tubes(yellow), the branched and yellow pistil, and yellow anther. From the results it can be concluded that Chrysanthemum morifolium Ramat has multiple the morphological differences and similarities of the flower morphology between the varieties.